Perkembangan Kebijakan Energi Nasional dan Energi Baru Terbarukan Indonesia - Savira Ayu Arsita; Guntur Eko Saputro; Susanto Susanto (CV. Syntax Corporation Indonesia, 2021)
Energy-related policies in Indonesia are increasingly dynamic, but in general they are starting to move towards a renewable energy transition. In order to reduce carbon emissions, Indonesia also regulates energy laws that can perpetuate the implementation of development programs based on renewable energy in the National Energy Policy. Through literature studies from legislation to the latest news, the author shows how the development of Indonesia's energy policy and especially in Indonesia's efforts in the transition to renewable energy. Law no. 30 of 2007 concerning Energy forms the basis for the development of regulations related to the design of new and renewable energy. In maximizing the new and renewable energy mix, the government is building renewable energy power plants, especially to overcome the problem of the electrification ratio, supporting the regulation of renewable energy, maximizing the National Energy Council and other institutions, setting specific targets, and holding a form of bilateral cooperation at the international level